Mechanism of arsenic release from realgar oxidation in the presence of dissolved oxygen: Effect of reactive oxygen species and light-induced transformation. (15th December 2022) - Liu, Lihu; Zhang, Ziwei; Zhang, Mingzhe; Yang, Xiong; Liu, Chengshuai; Qiu, Guohong
Abstract: Oxidative dissolution of realgar is an important cause of arsenic (As) pollution in waters and soils. Generally, environmental factors including dissolved oxygen (DO) and solar radiation can lead to the formation of reactive oxygen species (ROS) on As-bearing metal sulfide minerals, which significantly promotes mineral oxidation and As release. Realgar is a typical nonmetallic sulfide mineral with excellent photochemical properties. However, the possible formation mechanism of ROS and the effect of solar radiation on realgar oxidation and the subsequent As release remain elusive. Here, the processes of realgar oxidation and As release were studied under darkness and solar radiation, and the influence of DO and pH on the reaction process was also investigated. The decomposition of H2 O at the sulfur-defect sites and the oxidation of crystal surface As(II) by DO on realgar led to the formation of ROS including H2 O2 and OH, which play a critical role in realgar oxidation and As release. Under solar radiation, the reactions between electrons and O2 on light-excited realgar promoted the production of O2 − ; while the realgar oxidation and As release could be mainly ascribed to the transformation of realgar to pararealgar in the presence of DO. Under atmospheric conditions, the release ratio of total As in realgar suspension was 4.2% under darkness, and increased to 18.1% under solar radiation. Both higher DO concentration and pH facilitated the generation of ROS and light-induced transformation of realgar to pararealgar, thereby promoting As release. These results imply that the ROS generated on realgar can induce its oxidation and As release in underground aquifers and sediments, and solar radiation may be an important factor causing As pollution in realgar tailings. The findings improve the understanding of As pollution in sulfide mineral mining areas.